2016
DOI: 10.1186/s12879-016-1989-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of latent tuberculosis infection and predictive factors in an urban informal settlement in Johannesburg, South Africa: a cross-sectional study

Abstract: BackgroundSouth Africa has one of the highest burdens of latent tuberculosis infection (LTBI) in high-risk populations such as young children, adolescents, household contacts of TB cases, people living with HIV, gold miners and health care workers, but little is known about the burden of LTBI in its general population.MethodsUsing a community-based survey with random sampling, we examined the burden of LTBI in an urban township of Johannesburg and investigated factors associated with LTBI. The outcome of LTBI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 51 publications
8
28
0
1
Order By: Relevance
“…Our study also did not find any significant differences in LTBI prevalence between sexes, as noted in other high-risk populations, and in concordance with the study by TAYLOR et al [17] showing an identical percentage of males and females with LTBI. Studies involving children with LTBI found a higher proportion of males diagnosed with LTBI in China and Peru; those authors hypothesised that males could have spent more time socialising and interacting where the risk originated [18][19][20]. Our findings also suggest that children vaccinated with BCG have a 33% lower likelihood of developing LTBI (OR 0.67, 95% CI 0.37-1.21; p=0.18), albeit being nonsignificant.…”
Section: Discussionsupporting
confidence: 38%
See 1 more Smart Citation
“…Our study also did not find any significant differences in LTBI prevalence between sexes, as noted in other high-risk populations, and in concordance with the study by TAYLOR et al [17] showing an identical percentage of males and females with LTBI. Studies involving children with LTBI found a higher proportion of males diagnosed with LTBI in China and Peru; those authors hypothesised that males could have spent more time socialising and interacting where the risk originated [18][19][20]. Our findings also suggest that children vaccinated with BCG have a 33% lower likelihood of developing LTBI (OR 0.67, 95% CI 0.37-1.21; p=0.18), albeit being nonsignificant.…”
Section: Discussionsupporting
confidence: 38%
“…In addition to refugee children, one of the studies also included immigrants in the screening process for tuberculosis and LTBI, yielding an overall number of 67 334 children being examined with 12% prevalence of LTBI in total [17]. The prevalence of LTBI was found to be higher among older individuals, which is expected given the longer time period and potential for exposure to individuals having tuberculosis [5,18,19]. Our study also did not find any significant differences in LTBI prevalence between sexes, as noted in other high-risk populations, and in concordance with the study by TAYLOR et al [17] showing an identical percentage of males and females with LTBI.…”
Section: Discussionmentioning
confidence: 99%
“…CIs were derived by sampling parameter values for mine-specific transmission and immunity following previous infection. The FOI estimate for other South African residents in the model was found to be consistent with available ARTI measurements: 2.5–4.2% (across Western Cape, 2005, [ 40 ]), 3.8–4.5% (in Cape Town, 2005, [ 41 ]), 3.9–4.8% (in Cape Town, 2009, [ 42 ]), and 2.1–5.2% (in Johannesburg, 2013, [ 43 ]).…”
Section: Resultsmentioning
confidence: 59%
“…Progression to active TB, either through primary progression or reactivation of LTBI is 20-30 times higher in PLWH than those without [2]. In sub-Saharan Africa (SSA), LTBI in the general population is estimated to range from 34-75% [4][5][6], with no difference found by HIV status in recent studies [5,6]. However, TB preventive therapy is recommended for PLWH in high burden TB settings because of the high risk of progression to active disease [1, 2,7].…”
Section: Introductionmentioning
confidence: 99%